PRRT2 mutations and paroxysmal disorders. Issue 6 (9th February 2013) - Méneret, A.; Gaudebout, C.; Riant, F.; Vidailhet, M.; Depienne, C.; Roze, E.
<x xml:space="preserve">Abstract</x> In the past year, mutations in the PRRT2 gene have been identified in patients with paroxysmal kinesigenic dyskinesia and other paroxysmal disorders. We conducted a review of the literature on PRRT2 mutation‐associated disorders. Our objectives were to describe the wide clinical spectrum associated with PRRT2 mutations, and to present the current hypotheses on the underlying pathophysiology. PRRT2 mutations are associated with a wide range of clinical syndromes: the various paroxysmal dyskinesias, infantile seizures, paroxysmal torticollis, migraine, hemiplegic migraine, episodic ataxia and even intellectual disability in the homozygous state. The PRRT2 protein, through its interaction with SNAP‐25, could play a role in synaptic regulation in the cortex and the basal ganglia. The pathogenesis may be caused by PRRT2 loss of function, which may induce synaptic deregulation and neuronal hyperexcitability. However, this does not explain the phenotypic variability, which is likely modulated by environmental factors, modifier genes or age‐dependent expression. The clinical spectrum of PRRT2 mutations has expanded among paroxysmal disorders and beyond. Unraveling the molecular pathways linking the genetic defect to its clinical expression will be crucial for the diagnosis and treatment of these disorders.